2001
DOI: 10.1530/eje.0.1450087
|View full text |Cite
|
Sign up to set email alerts
|

Oestradiol and progesterone change beta3-adrenergic receptor affinity and density in brown adipocytes

Abstract: Objective: To check if the oestradiol-and progesterone-driven reduction in noradrenaline responsiveness of brown adipocytes is due to a reduction in either the density or the affinity of b 3 -adrenoceptors (b 3 -AR). b 1 /b 2 -AR were also studied. Design: Four groups of animals were considered. (i) control rats at thermoneutrality, (ii) coldacclimated rats, to determine b-AR under continuous sympathetic stimulation, which is known to decrease noradrenaline responsiveness, (iii) oestradiol-and (iv) progesteron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…This physiological situation is similar to the suppression of DIT observed in certain diet-induced obesity models [10]. It has been suggested that the increased plasma levels of 17β-estradiol and/or progesterone in pregnancy could be the main hormonal factors responsible for this inactivation of BAT thermogenesis [11,12]. On the other hand, the role of decreased plasma leptin levels on the inhibition of uncoupling protein expression in BAT during lactation has also been recently reported [13].…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…This physiological situation is similar to the suppression of DIT observed in certain diet-induced obesity models [10]. It has been suggested that the increased plasma levels of 17β-estradiol and/or progesterone in pregnancy could be the main hormonal factors responsible for this inactivation of BAT thermogenesis [11,12]. On the other hand, the role of decreased plasma leptin levels on the inhibition of uncoupling protein expression in BAT during lactation has also been recently reported [13].…”
Section: Introductionsupporting
confidence: 65%
“…This altered ratio could underlie the posterior decrease in UCP1 expression [13] as well as triglyceride deposition [30] in the tissue during late-pregnancy. Progesterone and 17β-estradiol, already showing elevated plasma levels during this period, have been shown in vivo to reduce the density of β 3 -ARs in BAT [12] hence being appealing candidates to be involved in the decreased β 3 -AR levels we report. However, the role of other hormones affecting β-ARs expression such as insulin [42] cannot be ruled out.…”
Section: Discussionmentioning
confidence: 52%
“…These cells express the ␤ 3 -AR at ϳ400 fmol/mg of protein (57)(58)(59). In untreated brown adipocytes, CL316243 potency is 10-fold lower than in CHO-K1 cells, despite only a 2.5-fold lower ␤ 3 -AR abundance, suggesting that the efficiency of cAMP generation is also decreased in the adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, estrogen deficiency is followed by a reduced UCP1 expression in BAT (38); and additionally, it has been shown that estrogen receptor knockout mice have a decrease in thermogenesis (39). In contrast, other reports assert that 17␤-estradiol and progesterone inhibit BAT thermogenesis (40,41), and change the affinity or density of ARs (42). From the present study, it seems to be clear that sex hormones can modulate the expression of AR in cultured brown adipocytes, and differences in vivo, compared with in vitro, could indicate a role for the sympathetic nervous system or changes in other hormones/metabolites.…”
Section: Discussionmentioning
confidence: 99%